Pengaruh Kompos dan Pupuk NPK 16:16:16 Terhadap Pertumbuhan dan Produksi Tanaman Terung Ungu (Solanum melongena L.) - Tumangger, Rade Karina; Zulfida, Ida; Alfarisi, Salman (JURNAL AGROPLASMA, 2025)
Eggplant (Solanum melongena L.) is a vegetable crop cultivated for its fruit, which is used as a food ingredient, either consumed fresh or processed into various dishes due to its pleasant taste. The decline in purple eggplant production can be caused by several factors, including poor soil fertility, inadequate cultivation practices, and improper fertilizer use. This study aims to analyze the effect of compost and NPK 16:16:16 fertilizer on the growth and yield of purple eggplant, as well as the interaction between the two types of fertilizers. The research was conducted at the experimental field of the Faculty of Agriculture, Universitas Pembinaan Masyarakat Indonesia, using a factorial randomized block design (RBD). The factors tested were compost doses (0, 1, 2, and 3 kg/plot) and NPK 16:16:16 doses (0, 50, 100, and 150 grams/plot). Eggplant growth data were measured at 14, 21, and 28 days after planting and analyzed using ANOVA followed by Duncan's multiple range test. The results showed that the best fertilizer treatment for eggplant growth was the combination of 3 kg compost/plot and 150 g NPK/plot, which resulted in a plant height of 70.3 cm. This indicates that the combination of both fertilizers significantly improved plant growth compared to other treatments. Keywords: eggplant, compos, NPK fertilizer